Improving Outcomes in Mental Health (IOMH)—an Australian longitudinal clinical study of families with children with neurodevelopmental problems: cohort profile - Mohan Karunanithi; Enda M Byrne; Naomi R Wray; Honey Heussler; Vanessa E Cobham; Nisreen Aouira; Anjali K Henders; Christel M Middeldorp; Sophie Howarth; Madhura Bhadravathi Lokeshappa; Leanne M Wallace; Daniel P Sullivan; et al. (BMJ Open)
Purpose Children with neurodevelopmental disorders (NDDs) such as autism spectrum disorder (ASD) and attention-deficit hyperactivity disorder (ADHD) face a range of challenges which impact their daily functioning and that of their family. NDDs are often associated with significant mental health problems which can influence the course. The Improving Outcomes in Mental Health cohort described in this article aims to investigate the risk factors for the persistence and severity of mental health problems in children with NDDs.Participants A total of 1084 families (primary caregivers and children) were recruited from the Child Development Program at the Children’s Health Queensland Hospital and Health Service in Brisbane, Australia. 1471 caregivers (female n=1036) participated in the study, which included 382 families with 2 or more caregivers participating. The children were predominantly male (71%), with the average age of all children 5.6 years.Findings to date The most prevalent child clinical diagnoses were ASD and ADHD, with half of children receiving more than one diagnosis. Caregiver reports indicated that children were experiencing clinical levels of depression (30.8%) and anxiety (27.6%). Approximately 39% of caregivers scored in the subclinical or clinical range for at least one Diagnostic and Statistical Manual of Mental Disorders measure, the majority reporting depressive problems.Future plans Future plans for this data set include analysis of environmental variables such as family structure, income, school achievements and leisure activities as risk factors for the persistence of mental health problems in children with NDDs. Genetic data will be used to provide insights into the heritability of mental illness and improve prediction.